2022
DOI: 10.1039/d1gc04825b
|View full text |Cite
|
Sign up to set email alerts
|

Divergent C(sp2)–H arylation of heterocycles via organic photoredox catalysis

Abstract: Introducing aryl moieties into heterocyclic scaffolds is a key step in the syntheses of natural products, drugs, and functional materials. Herein, we described an unprecedented photocatalytic direct C(sp2)-H arylation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 65 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…207 In 2022, Cui, Wu, and co-workers demonstrated that hypervalent iodonium ylides (39.3) can generate, upon oxidative quenching, aryl radicals and promote the late-stage arylation of heterocyclic species (39.2) (Scheme 39). 208 Naturally occurring coumarins were among the heterocyclic systems that underwent smooth C(sp 2 )−H late-stage arylation, for instance osthole and angelicin, extracted from plants of the genus Angelica. Notably, electron-rich trisubstituted alkene and benzofuran moieties remained intact.…”
Section: •-mentioning
confidence: 99%
“…207 In 2022, Cui, Wu, and co-workers demonstrated that hypervalent iodonium ylides (39.3) can generate, upon oxidative quenching, aryl radicals and promote the late-stage arylation of heterocyclic species (39.2) (Scheme 39). 208 Naturally occurring coumarins were among the heterocyclic systems that underwent smooth C(sp 2 )−H late-stage arylation, for instance osthole and angelicin, extracted from plants of the genus Angelica. Notably, electron-rich trisubstituted alkene and benzofuran moieties remained intact.…”
Section: •-mentioning
confidence: 99%
“…Kanchupalli group 35 Iodonium ylides were first employed for photocatalytic direct C(sp 2 )-H arylation of heterocycles without assistance of directing groups in our group (Scheme 28). 39 A wide scope of substrates 176, such as quinoxalin-2(1H)-ones coumarins, imidazopyridines, pyrazine, pyridazine and quinoxaline were transformed to the corresponding arylated products with excellent functional group tolerance. This protocol could also be applied to the late-stage functionalization of complex bioactive molecules such as TF-Angelicin, TF-Osthole, Tangeretin and Selexipag Impurity.…”
Section: C-h Bond Activationmentioning
confidence: 99%
“…Recently, Cui and Wu conducted the visible-light C(sp 2 )–H arylation of heterocycles with hypervalent iodine ylides as the arylating agents, eosin Y as the photocatalyst, and potassium carbonate as the base [ 64 ]. Among the synthesized heterocyclic scaffolds, five examples of imidazo[1,2- a ]pyridines were depicted with satisfactory yields ( Scheme 29 ).…”
Section: C–h Functionalizationmentioning
confidence: 99%